Does the Job Category Affect Employments’ Organizational Citizenship Behavior In Hospitals? (Bangladesh Journal of Medical Science, 2021)
Background and Objective: Organizational citizenship behavior (OCB) is one of facilitatingfactors in improving the quality of service in healthcare section. This study aimed at investigatingthe possible relationship between the job category and employees’ organizational citizenshipbehavior in some selected hospitals located in Northern Iran.Material and Methods: Thisapplied research was a descriptive-analytical cross-sectional survey conducted in 2016 amongtherapeutic and non-therapeutic/administrative employees working in 5 selected hospitals locatedin Golestan province, Iran. 320 employees were selected randomly by using Cochran samplingformula. The Persian version of Podsakoff’s standard scale for measuring the organizationalcitizenship behavior was used for data collection. The gathered data were analyzed by usingSPSS 18 and applying independent t-test and regression analysis.Results: The mean rate of nontherapeuticemployees’ organizational citizenship behavior (94.38±7.57) was higher than that oftherapeutic ones (93.98±9.36). The component altruism with 20.78±2.75 among therapeutic staffand the component conscientiousness with 20.87±2.09 among non-therapeutic staff were in thehighest rate. The mean differences of the components of the organizational citizenship behaviorwere not significant, The lowest rate belonged to the component civic virtue (14.28±2.03), butin altruism in which the difference was significantly positive (p= .039).Conclusion: Althoughthe job category has a low effect on the organizational citizenship behavior, the managersof healthcare centers can improve their employees’ organizational citizenship behavior byimproving organizational culture, work motivation and job satisfaction among the staff.Bangladesh Journal of Medical Science Vol.20(1) 2021 p.74-80